Síntese e atividade biológica in vitro de derivados triptamínicos e β-carbolínicos contendo o anel 4-tiazolidinona frente às células tumorais humas e ao Herpes simplex tipo 1 e, de derivados triazinos-indólicos frente à inibição da DYRK1A relacionada - Barbosa, Valeria Aquilino (2013)
Despite the advances in the treatment of the cancer, many of available medicines are not capable to eradicate the cancerous cells without affecting normal tissues. Also, no vaccine or effective antiviral drugs are currently available for prevention/treatment of many viral infections. In the same way, the medicines currently used in the treatment of the Alzheimer s disease (AD) cause several collateral effects, and have their effects minimized, in little time of use, in many patients. In the search for novel agents to treat these diseases, compounds with different skeleton have been explored, among them, triptamine, β-carboline and triazine-indole derivatives. The importance of the discovery of new antitumor and antiviral agents with more efficacy, low cytotoxicity and greater specificity, as well as, of new compounds that can retard and/or minimize the symptoms of the Alzheimer s disease, associated to the potentiality of triptamine, β-carboline and triazine-indole derivatives, led us to the development of the present work. . In the first part of the work, we carried out the synthesis and evaluation of the activity in vitro, towards human cancer cells lines and to the virus Herpessimplex type 1, of a series of tryptamine and β-carboline derivatives, having a 4-thiazolidinone ring coupled to its structures. The synthesis of N3-(2-phenylsubstituted-4-thiazolidinone)-tryptamine derivatives (51 a-h) was carried out via one-pot three-component condensation involving tryptamine, α-mercaptoacetic acid and appropriate aromatic aldehydes, by employing N,N-dicyclohexyl carbodiimide (DCC), in THF, as coupling agent (Methodology A) or a microwave-assisted condensation, using DMF as solvent (Methodology B). The synthetic routes for the β-carboline derivatives 60-62, 64, and 73-80 involved the preparation of the 1-(substituted phenyl)- β -carboline-3-carbohydrazides (56), whichare the synthetic intermediate for all series of desired derivatives. For this, the methyl tetrahydro- β -carboline-3-carboxylates 54 were prepared through Pictet-Spengler condensation of L-tryptophan methyl ester with appropriate aromatic aldehydes in acid media, and subsequent oxidized with sulfur, under xylene reflux, to furnish the methyl β -carboline-3-carboxylates (55).Conversion of 55 to 1-(substituted phenyl)- β -carboline-3-carbohydrazides 56 was carried out by reaction with hydrazine hydrate in ethanol. The series of 3-(carbonilhidrazono-4- thiazolidinone)-β-carboline derivatives 60, 61 and 62 were obtained through the reaction of 56 with potassium thiocyanate , ethyl isothiocyanate and phenyl isothiocyanate, respectively, followed by the reaction of corresponding thiosemicarbazides with ethyl bromoacetate, in presence of sodium acetate and potassium hydroxide. With excess of ethyl bromoacetate in the condensation step of the thiosemicarbazides 57, a new series of derivatives (64), containing an ethyl acetoacetoxyl group on the nitrogen of 4-thiazolidinone ring, was obtained. The derivatives of the 3-[amide-(2-substituted phenyl-4-thiazolidinone)] series (73 80) were prepared by the reaction of the imine intermediates 65-72 with mercaptoacetic acid, in the presence of ptoluenesulfonic acid, under reflux in toluene. All the synthesized compounds were characterized through the analysis of its spectroscopic data of RMN 1H, 13C, COSY and HSQC. The results of the biological assays in vitro showed that various of the synthesized tryptamine and β-carboline derivatives presented potent activity towards the virus Herpes simplex type 1 and against diverse human cancer cells lines tested. The second part of this work, developed in the Technische Universität Darmstadt, in Germany, as part of the doctoral sandwich, aimed the synthesis and evaluation of the inhibitory activity of DYRK1A of a series of 3-thiosubstituted -[1,2,4]-triazinoindole derivatives containing a methoxyl group in the benzenic ring of the indole unit. The series of 7- and 8-methoxy-3-thiosubstituted-triazino-indole derivatives (96 and 108) were obtained from the reaction of 5- and 6-methoxyisatin (93 and 105) with thiosemicarbazide, followed by the reaction of thiosemicarbazones corresponding with potassium carbonate, in water, for the formation of the triazino-3-thiol ring. Further reaction of the triazino-indolo-3-thiols 95, 99, 107 and 111 with alkyl or benzyl bromides in DMF afforded the 7- and 8-methoxy-3-thiosubstitutedtriazino-indole 96, 100, 108 and 112. For the preparation of derivatives 7- and 8-methoxy-triazinoindole S- and N-alkylated (100, 108 and 112), firstly was necessary the alkylation of the indole nitrogen of 93 and 105, and the synthetic route used was the same that those for the preparation of 96 and 108. The synthesized compounds were submitted to the Molecular Docking studies and those that presented a good interaction with protein DYRK1A were evaluated for the inhibitory activity of this protein. Among the evaluated compounds, those possessing the methoxy group at position-7 of the benzene ring presented more than 50% of inhibition of the protein DYRK1A.